2005
DOI: 10.1002/nme.1517
|View full text |Cite
|
Sign up to set email alerts
|

Use of higher‐order shape functions in the scaled boundary finite element method

Abstract: SUMMARYThe scaled boundary finite element method is a novel semi-analytical technique, whose versatility, accuracy and efficiency are not only equal to, but potentially better than the finite element method and the boundary element method for certain problems. This paper investigates the possibility of using higher-order polynomial functions for the shape functions. Two techniques for generating the higher-order shape functions are investigated. In the first, the spectral element approach is used with Lagrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…An additional benefit of the nodal quadrature lumping procedure is that a high-order element with Gauss-Lobatto-Legendre shape functions is formulated. This type of high-order element has been successfully applied to the scaled boundary finite-element method for statics by Vu and Deeks [35]. They demonstrated that higher rates of convergence can be obtained using p-refinement than using h-refinement.…”
Section: Lumped Coefficient Matrices [Ementioning
confidence: 96%
“…An additional benefit of the nodal quadrature lumping procedure is that a high-order element with Gauss-Lobatto-Legendre shape functions is formulated. This type of high-order element has been successfully applied to the scaled boundary finite-element method for statics by Vu and Deeks [35]. They demonstrated that higher rates of convergence can be obtained using p-refinement than using h-refinement.…”
Section: Lumped Coefficient Matrices [Ementioning
confidence: 96%
“…These sets of nodes are more clustered at the end of the elements with an asymptotic density proportional to (1−u 2 ) −1/2 as n →∞ [52]. More specifically, the n +1 LGL points are the roots of the polynomial (1−u 2 )L n (u) where u ranges from −1 to 1 and L n (u) is the Legendre polynomial of order n [54]. These points can be shifted to an arbitrary interval [a, b] through the relatioñ…”
Section: Higher Order Trial Functions-spectral Elementsmentioning
confidence: 98%
“…The Lagrange polynomial i corresponding to the ith node has the property Figure 4 shows the resulting seventh-order trial functions using eight nodes that are equally spaced in graph (a) while the LGL distribution is used in graph (b). These plots are generated over the range [−1, 1], and they match those in Reference [54]. Equation (16) comes from the typical form of Lagrange interpolation which is only recommended for a small number of nodes.…”
Section: Higher Order Trial Functions-spectral Elementsmentioning
confidence: 98%
“…Consequently, it helps to save time and computational effort in data preparation and storage. Different types of hierarchical shape functions were investigated [5], including the higher-derivative-based shape functions [11] and Lobatto polynomials [7,10]. The study recommended the use of the Lobatto polynomials due to their ability to produce accurate solutions for high polynomial order [5].…”
Section: Hierarchical Higher-order Elements In the Scaled Boundary Fimentioning
confidence: 99%